Cathodoluminescence of Ultrathin Twisted Ge1–xSnxS van der Waals Nanoribbon Waveguides. Issue 3 (6th December 2020) - Sutter, Peter; Khorashad, Larousse Khosravi; Argyropoulos, Christos; Sutter, Eli
Abstract: Ultrathin van der Waals semiconductors have shown extraordinary optoelectronic and photonic properties. Propagating photonic modes make layered crystal waveguides attractive for photonic circuitry and for studying hybrid light–matter states. Accessing guided modes by conventional optics is challenging due to the limited spatial resolution and poor out‐of‐plane far‐field coupling. Scanning near‐field optical microscopy can overcome these issues and can characterize waveguide modes down to a resolution of tens of nanometers, albeit for planar samples or nanostructures with moderate height variations. Electron microscopy provides atomic‐scale localization also for more complex geometries, and recent advances have extended the accessible excitations from interband transitions to phonons. Here, bottom‐up synthesized layered semiconductor (Ge1– x Sn x S) nanoribbons with an axial twist and deep subwavelength thickness are demonstrated as a platform for realizing waveguide modes, and cathodoluminescence spectroscopy is introduced as a tool to characterize them. Combined experiments and simulations show the excitation of guided modes by the electron beam and their efficient detection via photons emitted in the ribbon plane, which enables the measurement of key properties such as the evanescent field into the vacuum cladding with nanometer resolution. The results identify van der Waals waveguides operating in the infrared and highlight an electron‐microscopy‐based approach for probing complex‐shaped nanophotonic structures. Abstract : Ultrathin twisted Ge1– x Sn x S nanoribbons, realized via scalable vapor–liquid–solid growth over gold catalysts, provide a unique platform for probing guided excitonic waveguide modes in van der Waals semiconductors. Nanophotonic experiments using local electron‐beam excitation detect the confined modes in the plane of the layered crystal and enable the measurement of key properties such as the field distribution into the adjacent cladding layers.